Egoistic and altruistic behaviors in tobacco control campaign: the role of social media exposure, interpersonal communication and attitudes - Liu, Shiyu; Wu, Qiaofei; Luo, Xinyuan; Chen, Yu; Xu, Jing (Frontiers in Communication, 2023)
Introduction A growing body of research has examined the relationship between media exposure to health campaign information and health behaviors, yielding inconsistent findings. To address this inconsistency, it is crucial to investigate the underlying mediation and moderation mechanisms. Building upon the social diffusion model, this study explores the mediating role of interpersonal communication and the moderating role of attitudes in the relationships between health behavioral outcomes and exposure to campaign information. Method A tobacco control social media campaign were conducted and assessed via an online survey. Specifically, the survey was conducted from the day after the end of the campaign. Respondents were recruited via Sojump using convenience and snowball sampling. Eligible participants were non-smokers and quitters residing in China and had been exposed to the campaign information. Data were analyzed using the R software. Results A total of 326 eligible participants were included in the final analysis. The results suggest that social media exposure to campaign information is indirectly associated with both egoistic and altruistic behavioral intentions through interpersonal communication. However, attitudes toward tobacco control weaken the association between social media exposure to campaign information and interpersonal communication about tobacco risks. Furthermore, the indirect effect of social media exposure to campaign information on egoistic and altruistic behavioral intentions, mediated by interpersonal communication about tobacco risks, is contingent upon attitudes toward tobacco control. Conclusion This study tests and supports the proposition that interpersonal communication mediates the effects of campaign information exposure on health behaviors in the context of China, which contributes to the existing literature on the health effects of campaign information exposure and provides implications for the design of health campaigns to more effectively promote healthy behaviors.